Linking the government expenditures to the achievement of the Europe 2020 strategy indicators. Evidence from Central and Eastern European Countries - Bădîrcea, Roxana Maria; Manta, Alina Georgiana; (Florea) Doran, Nicoleta Mihaela; Manta, Florin Liviu (Technological and Economic Development of Economy, 2022)
In order to evaluate the degree of sustainable development at CEEC (Central and Eastern European Countries) by means of an aggregate indicator and to determine if the government expenditures in the field of environment, environment protection, fuel, energy, education and social protection could influence the achievement of the Europa 2020 targets, a data panel of 10 CEEC for 2007–2018 period was analysed through Fully Modified Ordinary Least Squares (FMOLS) method and a Vector Error Correction Model (VECM). To calculate the indicator, an algorithm that included six steps was used. The results of the study show, on long-term, statistically significant correlations between the target indicator and all the selected variables, except for the government expenditures with the education variable. However, on short-term, there were identified strong connections reflected in bidirectional causality between government expenditures with social protection and the target indicator. Also, on short-term, a strong causal relationship was identified from target indicator to the total government expenditures for education, from the environmental protection government expenditures to the government expenditures for social protection and from the total government expenditures for social protection to the total government expenditures for education.First published online 17 March 2022